Consumer behaviour : the Canadian perspective - Kindra, Gurprit S. 1954- (Nelson Canada, 1994)
Consumer behaviour defined. The dynamics of consumer behaviour: an introductory example. Modelling consumer behaviour. Perceptual phenomena and marketing strategy. the consumer as a learner. Consumer attitudes: formation and change. Needs, values, and lifestyles. Cultural influences on consumer behaviour. Ethnic groups in Canada. Consumer behaviour in French Canada. Reference groups...